Biotesting of titanium tetrapolyethylene glycolate in 10 molar excess on granulosa cell culture of porcine follicles - A. O. Prituzhalova; T. I. Kuzmina; T. G. Khonina; U. S. Nikulina (Аграрная наука Евро-Северо-Востока)
The effect of titanium tetrapolyethylene glycolate dissolved in polyethylene glycol (ratio 1:10) (abbreviated TTPEG*10PEG) on granulosa cells (GC) of the antral ovarian follicles of Sus scrofa domesticus in the dynamics of in vitro culture was assessed. Granulosa cells aspirated from post mortem ovarian porcine follicles (ø 3-5 mm) obtained at the Tosnensky Meat Processing Plant, were cultured without and in the presence of 0.1, 0.01 and 0.001 % TTPEG*10PEG.  After 22 and 44 hours, the GC were analyzed by flow cytometry. A comprehensive analysis of viability indicators (mitochondrial activity, apoptosis), as well as the generation of reactive oxygen species (ROS) in the GC after exposure to TTPEG*10PEG, revealed that the addition of 0.1 % TTPEG*10PEG to the culture medium after 22 and 44 hours causes disturbances in the functional activity of the GC, accompanied by a decrease of mitochondrial membrane potential compared to control (by 8 and 9 %, respectively, p<0.05) and cell death (the proportion of cells in apoptosis was 45 and 41 %, respectively, p<0.001). In the groups cultured in the presence of 0.01 % and 0.001 % TTPEG*10PEG, no significant differences in the level of GC in the state of apoptosis were detected when cultured for either 22 or 44 hours. At the same time, an increase in mitochondrial  activity was shown in these groups in comparison with the control and the group containing 0.1 % TTPEG*10PEG (by 11 and 13 %, respectively, after 22 hours, p<0.001 and by 15 and 27 % after 44 hours, p< 0.001). No significant differences were found between the study groups in the rate of ROS generation in cells. In general, a dose-dependent negative effect  of TTPEG*10PEG (0.1 %) was identified. TTPEG*10PEG at concentrations of 0.01 and 0.001% did not have a destructive effect on the studied cell population, which indicates the possibility of using TTPEG*10PEG at the above concentrations (0.01 and 0.001 %) to simulate the composition of media used in porcine granulosa cells culture systems.